(y-11) -(y+6)=6y
y - 11 - y - 6 = 6y
y - y - 6 - 11 = 6y
0 - 17 = 6y
6y = -17
y = -17/6
The answer is D) -17 over 6
2006-11-11 16:06:35
·
answer #1
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
1⤋
D
(y-11)-(y+6)=6y
y-11+(-y)-6=6y
-17=6y
-17/6=y
2006-11-12 00:00:04
·
answer #2
·
answered by asslpman 2
·
1⤊
0⤋
The answer I got is D. -17/6
(y-11)- (y+6) = 6y
distribute the negative
y-11-y-6= 6y
'y's cancel out on left
-11-6 = 6y
-17=6y
divide by 6
y=-17/6
2006-11-11 22:50:51
·
answer #3
·
answered by a.t. 1
·
1⤊
0⤋
Use the distributive property (no, the properties never go away) to get rid of the (), so you get y-11-y-6=6y. The second step is combine like terms, so your y's on the left side go away y-y, and you have -11-6, which is -17=6y, divide by the 6 on the right and the anwer is D
2006-11-11 23:06:09
·
answer #4
·
answered by Dave & T 1
·
1⤊
0⤋
D which is -17/6
get rid of the parentheses and you will have y-11-y-6 = 6y
combine the ys on the left side qand combine the numbers on the left side and you will have y-y -11-6 = -17 = 6y
Divide both sides by 6 and you will have: -17/6 = y
2006-11-11 22:51:19
·
answer #5
·
answered by Rich Z 7
·
1⤊
0⤋
y-11-y-6=6y
-17=6y
dividing by 6
y=-17/6choice D
2006-11-11 22:49:11
·
answer #6
·
answered by raj 7
·
1⤊
0⤋
I will start you out:
(y - 11) - (y+6) = y - 11 - y - 6
= -17
you do the rest
2006-11-11 22:49:04
·
answer #7
·
answered by banjuja58 4
·
0⤊
1⤋
(y-11)-(y+6)=6y
y-11-y-6=6y
-17=6y
y=-17/6
Approx.=-2.83
So the answer is D).
2006-11-12 00:26:31
·
answer #8
·
answered by Mysterious 3
·
1⤊
0⤋
(y-11)-(y+6)=6y
y-y-11-6=6y
-17=6y
y=-17/6
D)-17 over 6
2006-11-11 22:53:27
·
answer #9
·
answered by ulaanbaatar17 1
·
1⤊
0⤋
its D its has to be 100% sure
Y-11-Y-6
Y-Y= oY
so -17=6y
-17/6
2006-11-11 22:49:03
·
answer #10
·
answered by sap6902004 2
·
0⤊
1⤋